The asylum, the workhouse, and the voice of the insane poor in nineteenth century England - Bartlett, Peter (Elsevier, 1998)
The history of psychiatry is not merely the history of psychiatrists; it is also the history of patients. In this paper, admission records and case notes of a county asylum are used to consider the attitudes of those confined within it, and how the asylum was understood by patients relative to other options for care, most notably the workhouse.